Pengaruh Pengungkapan Green Intellectual Capital dan Sustainability Reporting Disclosure terhadap Kinerja Keuangan - Zuhdi, Abid Maulana; Syachyadi, Ilham; Astuti, Christina Dwi (BUDGETING : Journal of Business, Management and Accounting, 2024)
The purpose of this research is to examine and analyze the effect of Green Intellectual Capital Disclosure and Sustainability Reporting Disclosure on Financial Performance. The research population is Primary Sub-Sector Companies listed on the Indonesia Stock Exchange during 2019-2022. The type of data used is secondary data, namely data derived from financial reports and annual reports. The purposive sampling method used in this study obtained 328 samples and a total sample of 207 companies from 2019-2022. This study uses the Multiple Linear Regression model. The results of this study indicate that Green Human Capital, Green Structural Capital has a positive effect on company performance, Green Relation Capital and Sustainability Reporting Disclosure has no effect on financial performance. Keywords: Financial Performance, Green Intellectual Capital, Sustainability Reporting Disclosure.